Water-Saving Technology in Sandy Soil Conditions (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The article describes the possibilities of improving the moisture regime of the soil and reducing water consumption by co-planting crops (joint care) in the conditions of sandy soils of the desert region.